Analisis Kadar Kafein dan Antioksidan Kopi Robusta (Coffea canephora) Terfermentasi Saccharomyces cerevisiae - Yogi Rabani RS, I Gusti Agung; Elza Fitriani, Pande P. (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPA, 2022)
Robusta coffee is one of Indonesia's premier commodities known both domestic and international markets. Coffee beans are known to contain polyphenol, a flavonoid substance listed as one of the strong antioxidants, particularly chlorogenic acid (cholorogenic acid), which is one of the known resistance to free radical conditions. The study is aimed at recognizing the effect of increasing yeast and optimizing time fermentation on caffeine content and antioxidant activity on robusta coffee beans. The study is an experimental study aimed at recognizing the effects of increased yeast and longer fermentation on the characteristics of pubic coffee covering acidity (ph), total caffeine, total phenol, and antioxidal activity. Research design is a complete random design (ral). The factors noted are the five degrees of yeast concentration (k), the concentration of leaven 0% (k0), the concentration of leaven 1% (k1), the concentration of leaven 2% (k2), the concentration of yeast 3% (k3), and the concentration of yeast 4% (k4). Analysis of each treatment involves degrees of acidity, total caffeine, water level, and phytocyination test. Fingerprint analysis will show the best treatment of the effects of yeast increases and longer fermentation. Studies are expected to provide information on the best quality of fermented robusta coffee. Based on research that has been compared to the conditions of the characteristic characteristic of fermented arabic-ground coffee using s. cerevisiae with a concentration of 0%, 1%, 2%, 3% and 4% according to coffee characteristics 01-3542-2004 based on water sni 2.33-1.68% b/b, the coffee saris 301-30%35% b/b and caffeine level 1.18-1,01% b/b. The fermentation process reduces the pH and sugar reduction and the formation of ethanol.